Periodontal status in patients with chronic skin diseases: a pilot study - Nguyen, Hao; Pham, Nguyen; Vo, Thuy; Duong, Huong; Ho, Hoa; Pham, Nhi; Huynh, Nam; Nguyen, Thuy (Chulalongkorn Medical Journal, 2025)
Background: Many skin diseases, especially those that also involve oral mucosa lesions, might play an essential role in the etiopathogenesis of oral health and mucocutaneous inflammation. The presence of these oral lesions may make it challenging to maintain satisfactory oral hygiene, which increases plaque accumulation and the risk of developing periodontal disease. Objectives: This study evaluated and compared the periodontal status of patients with chronic skin disease (CSD) with that of healthy controls. Methods: This study included 109 patients and 37 healthy controls. The evaluated parameters included the bleeding on probing index (BOP), periodontal pocket depths (PPD), clinical attachment level (CAL), simplified debris index (DI), simplified calculus index (CI), and the presence of oral lesions. Clinical parameters were measured and compared between the two groups using the chi-square test, t-test, and a non-parametric test. Results: Patients with CSD had significantly higher BOP and a lower percentage of teeth with CAL d” 3 mm compared with those in the control group. Furthermore, CAL > 6 mm was only presented in the group of patients with CSD. There were no significant differences in the PPD, PI, and CI parameters and oral lesions between the two groups. Conclusion: This pilot study revealed that the periodontal status of patients with CSD was worse than that of healthy controls. These results suggest that patients with CSD appear to be more at risk for the development and progression of periodontal diseases.